2003
DOI: 10.1039/b307544c
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of DNA-tethered ruthenium complexes that self-assemble into linear arrays

Abstract: Ruthenium(II) bis(terpyridine) complexes have been prepared with two triethylene glycol linkers to which DNA sequences have been attached; hybridization at various complex ratios results in linear arrays of varying lengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Towards this end, 1-deazaadenine (D) and thymine (T) were chosen as complementary nucleobases. [50] Earlier reports had suggested that the oligonucleotides d(D 20 ) and d(T 20 ) associate via the Hoogsteen edge of the purine base to form a double helix. [123,124] Scheme 7 shows how a metal-ion-mediated base pair is derived from such a Hoogsteen pair by the substitution of a proton by a metal ion.…”
Section: Base Pairs Mediated By Hydrogen Bonding and Metal-ion-bindingmentioning
confidence: 98%
“…Towards this end, 1-deazaadenine (D) and thymine (T) were chosen as complementary nucleobases. [50] Earlier reports had suggested that the oligonucleotides d(D 20 ) and d(T 20 ) associate via the Hoogsteen edge of the purine base to form a double helix. [123,124] Scheme 7 shows how a metal-ion-mediated base pair is derived from such a Hoogsteen pair by the substitution of a proton by a metal ion.…”
Section: Base Pairs Mediated By Hydrogen Bonding and Metal-ion-bindingmentioning
confidence: 98%
“…The ratio of A:B and B:A mainly dictate the structure of assembly upon hybridisation. For example a ratio of A:B or B:A of 2:1 results in A 2 B or B 2 A trimer as the major component and a longer linear array is formed when the ratio of complexes approaches to 1:1 20. By using a more versatile synthetic strategy, we were able to prepare symmetrical homoleptic metal‐complex/ODN building block (i.e., with one DNA strand on each ligand such as A or B in Figure 4 A).…”
Section: Structural Diversity Of Metal‐complex/odn Conjugatesmentioning
confidence: 99%
“…Examples of structural diversity of metal-complex/ODN conjugates upon different tethering approaches of ODNs to different metal complexes (taken with permission from references[20][21][22][23][24][25][26][27]). …”
mentioning
confidence: 99%
“…Ni 2þ coordination to cyclam was used only to increase the rigidity of the junction (168). Metal binding to tpy-modified ssDNA led to octahedral [Fe(tpy) 2 ] 2þ complexes (169) or [Ru(tpy) 2 ] 2þ complexes (170), which functioned as two-arm DNA junctions [ Fig. 18(b)].…”
Section: Extended Hybrid Inorganic-nucleic Acid Nanostructuresmentioning
confidence: 99%
“…18(b)] (169). Hybridization by slow cooling of 1:1 mixtures of two-arm DNA junctions based on bpy-Ru 2þ or tpy-Ru 2þ complexes that had intramolecularly identical but intermolecularly complementary DNA arms led to infinite, linear DNA polymer formation (170,172). In contrast, room temperature hybridization of the same two-arm DNA junctions based on bpy-Ru 2þ led to the formation of a mixture of structures, the majority of which were dimeric and cyclic [ Fig.…”
Section: Extended Hybrid Inorganic-nucleic Acid Nanostructuresmentioning
confidence: 99%